Talk with the Bots Gesprächsroboter und Social Bots im Diskurs - Hug, Theo; Pallaver, Günther (Edited Volume Series, 2018)
More and more often, software communicates with and for us. Bots often take over complex tasks unnoticed, and virtual assistants process spoken language. Technological developments now allow us to integrate the services of digital, often voice-based assistance systems into our everyday lives. Particularly in the field of political propaganda and public relations, social bots have for some time been gaining dubious notoriety. Used as an instrument for opinion making, they automatically spread messages in so-called "social" networks. This interdisciplinary volume addresses this issue and seeks answers to questions such as the following: How can we distinguish interaction with artificial intelligences from that with humans? To what extent is this important? What does this development mean for everyday life and for the field of communication? What is the significance of the widespread use of bots as a new interface between humans and machines?; Immer öfter kommuniziert Software mit und für uns. Bots übernehmen oft unbemerkt komplexe Aufgaben und virtuelle Assistenzen verarbeiten die gesprochene Sprache. Die Technologieentwicklung gestattet uns mittlerweile, die Dienste von digitalen, oftmals sprachbasierten Assistenzsystemen in unseren Alltag zu integrieren. Besonders im Bereich der politischen Propaganda und Public Relations sind Social Bots seit einiger Zeit zu zweifelhafter Berühmtheit gelangt. Eingesetzt als Instrument zur Meinungsmache verbreiten sie automatisiert Nachrichten in sogenannten "sozialen" Netzwerken. Der interdisziplinär ausgerichtete Band befasst sich mit dieser Thematik und sucht nach Antworten auf Fragen wie die folgenden: Wie können wir die Interaktion mit künstlichen Intelligenzen von jener mit Menschen unterscheiden? Inwieweit ist das wichtig? Was bedeutet diese Entwicklung für das Alltagsleben und für den Bereich der Kommunikation? Welche Bedeutung hat der verbreitete Einsatz von Bots als neue Schnittstelle zwischen Mensch und Maschine?